2013
DOI: 10.3389/fpsyt.2013.00073
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation to Maintain Treatment Response to Electroconvulsive Therapy in Depression: A Case Series

Abstract: Electroconvulsive therapy (ECT) is the most effective treatment for a refractory major depression in the context of both unipolar and bipolar affective disorders. However, the relapse rate within the first 6 months after a successful course of ECT to treat a depressive episode can be as high 50%. Evidence-based strategies to prevent relapse have partial efficacy and are associated with problematic adverse effects limiting their use as long-term treatments. Repetitive transcranial magnetic stimulation (rTMS) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The H1-coil is the most tested coil, and every dTMS center should have one. It should be used for patients with depression who have failed any number of medications before trying ECT, and it can be used after ECT as a maintenance strategy in lieu of ECT maintenance [97,98]. There is early data suggesting that higher numbers of pulses may be helpful for patients with psychotic depression or schizoaffective disorder depressive phase as well as patients who failed ECT [42,43], the H1 is helpful for the negative symptoms of schizophrenia [46,62].…”
Section: Expert Commentarymentioning
confidence: 99%
“…The H1-coil is the most tested coil, and every dTMS center should have one. It should be used for patients with depression who have failed any number of medications before trying ECT, and it can be used after ECT as a maintenance strategy in lieu of ECT maintenance [97,98]. There is early data suggesting that higher numbers of pulses may be helpful for patients with psychotic depression or schizoaffective disorder depressive phase as well as patients who failed ECT [42,43], the H1 is helpful for the negative symptoms of schizophrenia [46,62].…”
Section: Expert Commentarymentioning
confidence: 99%
“…For instance, Hadley et al [19] stressed the potential of HF-rTMS in rapidly reducing suicidal ideation, similarly to electroconvulsive therapy (ECT). Furthermore, two recent studies [7,35] evaluated the effectiveness of rTMS as maintenance treatment after acute ECT, reporting encouraging results [25].…”
Section: Introductionmentioning
confidence: 99%
“…Milev et al, 2016), they do not address the substitution of effective ECT. Two small case series (Cristancho et al, 2013; Noda et al, 2013) have found that rTMS may be successfully substituted (such that it maintains or improves clinical status) for maintenance ECT terminated due to tolerability issues. This suggests that consideration of a trial of rTMS in this case was perhaps appropriate, albeit somewhat experimental.…”
Section: Sequencing Of Treatmentmentioning
confidence: 99%